(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To identify the main difficulties reported by patients and caregivers in the use of clean intermittent catheterization described in the scientific literature. Methods: Scoping review with studies published in Portuguese, English or Spanish, without date limit, in electronic databases and digital libraries, using descriptors and keywords. Results: 790 studies were identified, including 34 studies published between 1984 and 2019. The main difficulties reported in performing clean intermittent catheterization were related to catheter insertion, pain, discomfort, urethral trauma, public bathrooms with inadequate facilities, physical difficulties and lack of access to necessary inputs. Conclusion: The studies analyzed show the difficulties that patients who use clean intermittent catheterization and their caregivers face on a daily basis, which are related to intrinsic and extrinsic, institutional and governmental factors and can decrease satisfaction and adherence to rehabilitation programs bladder, with an impact on the quality of life of patients and their caregivers. Therefore, it highlights the need for health education for the proper teaching of performing clean intermittent catheterization, emphasizing the importance of the nurse’s role in this process.